2009
DOI: 10.7551/mitpress/8402.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Hanging Out, Messing Around, and Geeking Out

Abstract: An examination of young people's everyday new media practices—including video-game playing, text-messaging, digital media production, and social media use. Conventional wisdom about young people's use of digital technology often equates generational identity with technology identity: today's teens seem constantly plugged in to video games, social networking sites, and text messaging. Yet there is little actual research that investigates the intricate dynamics of youths' social and recreational u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
3
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(198 citation statements)
references
References 0 publications
7
169
3
9
Order By: Relevance
“…Young people go to online spaces to learn about the issues and challenges they are facing in their lives (Ito et al 2010). In my doctoral research that focused on studying 11 young people's usage of social media for learning about and taking action on local environmental issues, the majority said that climate change is their number one concern (Field 2017).…”
Section: Two Educational Shiftsmentioning
confidence: 99%
“…Young people go to online spaces to learn about the issues and challenges they are facing in their lives (Ito et al 2010). In my doctoral research that focused on studying 11 young people's usage of social media for learning about and taking action on local environmental issues, the majority said that climate change is their number one concern (Field 2017).…”
Section: Two Educational Shiftsmentioning
confidence: 99%
“…The theories and practices of new media literacies we had been discussing were unfolding before our eyes. For example, students reported that technology-rich environments were "rich" due in part to the material and human resources that allow for digitally-mediated interactions and networked activities (Ito, 2010;Ito et al, 2013;Lister et al, 2009). Students also noted the variability in spatial design conducive for specific purposes, including physical set ups for messing around as an element of learning.…”
Section: Experiential Learning To Poster Projectmentioning
confidence: 96%
“…As we moved toward weeks 5 to 8 of the semester, different articles and studies of new media literacies in youth's lives provided practical insights (Ito, 2010;Palfrey & Gasser, 2008;Scott & White, 2011). Genres of participation such as hanging out, messing around, and geeking out offered a framework for us to consider.…”
Section: Experiential Learning To Poster Projectmentioning
confidence: 98%
“…This is sometimes referred to as "collaborative remixability," (Dybwad, 2005). Jenkins (2006;Jenkins et al, 2007) and Ito (2010) have written extensively about the role that youth have played in leveraging online communities to repurpose media scripts and create new dynamic communities that are civic and participatory in and of themselves. Manovich (2005) argued extensively for the central role that repurposing and sharing information will play in networked societies of the 21st century.…”
Section: Media Literacy's Role In Participatory Culturementioning
confidence: 99%